Physiological effects of tangeretin and heptamethoxyflavone on obese C57BL/6J mice fed a high-fat diet and analyses of the metabolites originating from these two polymethoxylated flavones - Nery, Marina [UNESP]; Ferreira, Paula S. [UNESP]; Gonçalves, Danielle R. [UNESP]; Spolidorio, Luis C. [UNESP]; Manthey, John A.; Cesar, Thais B. [UNESP] (Wiley, 2021)
Two compounds from citrus peel, tangeretin (TAN) and 3′,4′,3,5,6,7,8-heptamethoxyflavone (HMF), were investigated for their abilities to repair metabolic damages caused by an high-fat diet (HFD) in C57BL/6J mice. In the first 4 weeks, mice were fed either a standard diet (11% kcal from fat) for the control group, or a HFD (45% kcal from fat) to establish obesity in three experimental groups. In the following 4 weeks, two groups receiving the HFD were supplemented with either TAN or HMF at daily doses of 100 mg/kg body weight, while the two remaining groups continued to receive the standard healthy diet or the nonsupplemented HFD. Four weeks of supplementation with TAN and HMF resulted in intermediate levels of blood serum glucose, leptin, resistin, and insulin resistance compared with the healthy control and the nonsupplemented HFD groups. Blood serum peroxidation (TBARS) levels were significantly lower in the TAN and HMF groups compared with the nonsupplemented HFD group. Several differences occurred in the physiological effects of HMF versus TAN. TAN, but not HMF, reduced adipocyte size in the mice with pre-existent obesity, while HMF, but not TAN, decreased fat accumulation in the liver and also significantly increased the levels of an anti-inflammatory cytokine, IL-10. In an analysis of the metabolites of TAN and HMF, several main classes occurred, including a new set of methylglucuronide conjugates. It is suggested that contrasts between the observed physiological effects of TAN and HMF may be attributable to the differences in numbers and chemical structures of TAN and HMF metabolites.
Keywords: citrus; flavonoids; inflammation; metabolites; obesity; oxidative stress